Method for manufacturing grain-oriented electrical steel sheet and annealing release agent used therefor
Patent Information
- Application Number
- CN202280012381.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-04
- Filing Date
- 2022-02-02
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-02-02
AI Technical Summary
但是,在钢的成分组成包含上述的Ti、Nb和Ta等增强元素的情况下,在该纯化退火中未充分纯化,在钢中作为氮化物、碳化物析出而残留
[0032]根据本发明,由于能够充分纯化抑制剂增强元素,因此能够制造磁特性良好的取向性电磁钢板,从而能够极大地有助于取向性电磁钢板的品质提高。
Smart Images

Figure BDA0004364564590000051 
Figure BDA0004364564590000101 
Figure BDA0004364564590000111
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing oriented electromagnetic steel sheets for cores of transformers and other electrical equipment, and particularly to a method for manufacturing oriented electromagnetic steel sheets with excellent magnetic and coating properties by improving the annealing separating agent coated on a decarburized annealed steel sheet.
[0002] In addition, the annealing separating agent used in the manufacturing method of the aforementioned oriented electromagnetic steel sheet is also involved. Background Technology
[0003] The manufacturing process of oriented electromagnetic steel sheets generally involves hot rolling of the steel billet followed by cold rolling, then decarburization annealing, and finally final annealing for secondary recrystallization. During the final annealing, secondary recrystallization occurs, generating coarse grains with their easy magnetization axes aligned in the rolling direction of the steel sheet.
[0004] To prevent sintering of the steel plate during the lengthy final annealing process, an annealing separating agent primarily composed of MgO is typically applied to the steel plate before annealing. In addition to acting as an annealing separating agent, the MgO also reacts with the SiO2-based oxide layer formed during decarburization annealing to form a magnesium olivine film.
[0005] Furthermore, the various properties of annealing separating agents affect the base iron portion, such as the formation and growth behavior of precipitates and grain growth, thus significantly altering the product characteristics of oriented electromagnetic steel sheets. For example, if too much moisture is introduced during the slurrying of the annealing separating agent, the steel sheet will be oxidized, its magnetic properties will deteriorate, or point defects will appear in the coating. Additionally, it is known that impurities contained in the annealing separating agent can penetrate into the steel during annealing, altering secondary recrystallization behavior and coating formation behavior.
[0006] However, in recent years, with the increasing demand for energy conservation, the requirement to further improve the magnetic properties of grain-oriented electromagnetic steel sheets has become increasingly strong. As one of the countermeasures, a technique has been proposed to add elements such as Ti, Nb, and Ta to the steel composition to enhance grain growth inhibition.
[0007] However, while adding these elements can generate uniformly oriented secondary recrystallized grains during grain growth, there is a problem that these elements cannot be purified. Typically, after secondary recrystallization annealing, a purification annealing at around 1200°C is performed, during which inhibitors such as AlN and MnS decompose and are removed from the steel. However, if the steel composition includes reinforcing elements such as Ti, Nb, and Ta, these elements may not be sufficiently purified during the purification annealing process and may precipitate as nitrides and carbides, remaining in the steel. If such residues occur, these precipitates can hinder the movement of magnetic domain walls during product use, increasing iron losses and preventing the desired energy-saving effect from being achieved.
[0008] To address this problem, many techniques have been proposed to improve the purification of inhibitor elements. For example, Patent Document 1 proposes a method to facilitate decarburization by performing unwinding annealing in a humid atmosphere after secondary recrystallization.
[0009] In addition, Patent Document 2 proposes a method to promote purification by reducing the nitrogen partial pressure in the final annealing atmosphere.
[0010] Patent document 3 discloses a method for cooling a specific temperature range of a steel sheet after final annealing in an atmosphere of hydrogen and an inert gas.
[0011] Patent document 4 discloses a method for purification annealing in a mixed atmosphere of H2-N2.
[0012] Existing technical documents
[0013] Patent documents
[0014] Patent Document 1: Japanese Patent Application Publication No. 2008-115421
[0015] Patent Document 2: Japanese Patent Application Publication No. 11-158557
[0016] Patent Document 3: Japanese Patent Application Publication No. 2006-193798
[0017] Patent Document 4: Japanese Patent Application Publication No. 9-184017 Summary of the Invention
[0018] However, although the method described in Patent Document 1 can effectively decarburize, elements such as Nb and Ta still remain in the steel. These elements remaining in the steel combine with small amounts of nitrogen, oxygen, carbon, etc. in the steel, and sometimes cause magnetic aging during product use.
[0019] In the method described in Patent Document 2, although the purification of nitrogen is improved, elements such as Nb and Ta still remain in the steel. These elements combine with carbon and other materials, which can sometimes cause magnetic aging.
[0020] Although the method described in Patent Document 3 can prevent nitriding during the cooling of the final annealing, the residual elements such as Nb and Ta still cause magnetic aging.
[0021] In the method described in Patent Document 4, Ti can be inhibited from penetrating into the steel by fixing Ti in the film, but the effect is still limited because it cannot purify the Ti, Nb and other substances originally present in the base iron.
[0022] In addition to these, although various methods have been designed to improve poor purification and reduce iron loss, they are all insufficient and it is difficult to obtain the desired characteristics.
[0023] The present invention was made in view of the above circumstances, and its object is to simultaneously provide a method for manufacturing an orientation-oriented electromagnetic steel sheet that can effectively improve iron loss by improving the purification of inhibitor reinforcing elements through the improvement of annealing separating agent, as well as the above-mentioned improved annealing separating agent.
[0024] The essential elements of this invention are as follows.
[0025] 1. A method for manufacturing a grain-oriented electromagnetic steel sheet, characterized in that the grain-oriented electromagnetic steel sheet is heated and hot-rolled using a slab, subjected to one or more cold rolling processes with intermediate annealing, followed by a recrystallization annealing, and then coated with an annealing separating agent before final annealing.
[0026] The slab for the aforementioned oriented electromagnetic steel sheet has the following composition: containing C: 0.01–0.09% by mass, Si: 2.00–4.00% by mass, Mn: 0.03–0.25% by mass, further containing a total of 0.002–0.025% by mass of one or more selected from Nb, V, and Ti, with the remainder being Fe and unavoidable impurities.
[0027] The above-mentioned annealing separating agent is based on MgO and contains a composite oxide in the range of 1 to 10 parts by mass relative to MgO: 100 parts by mass. The composite oxide contains one or more elements selected from Group 1: Fe, Mn, Al and Ca and Group 2: Zr, Ta, Mo and Nb.
[0028] 2. The method for manufacturing oriented electromagnetic steel sheet according to 1 above, wherein the maximum temperature reached by the final annealing is set to 1210°C or higher.
[0029] 3. The method for manufacturing the oriented electromagnetic steel sheet according to 1 or 2, wherein the slab for the oriented electromagnetic steel sheet, in addition to the above-mentioned composition, further contains, in addition to, components selected from Al: 0.004–0.040 wt%, N: 0.002–0.010 wt%, S: 0.002–0.030 wt%, Se: 0.002–0.030 wt%, Ni: 0.01–1.50 wt%, and Cr: 0.01–0.50 wt%. One or more of the following: Cu: 0.01–0.50 wt%, P: 0.005–0.100 wt%, Sb: 0.005–0.100 wt%, Sn: 0.005–0.100 wt%, Bi: 0.001–0.050 wt%, Mo: 0.005–0.100 wt%, B: 0.0002–0.0025 wt%, and Te: 0.0005–0.0100 wt%.
[0030] 4. An annealing separating agent, characterized in that it is the annealing separating agent used in the manufacturing method of the oriented electromagnetic steel sheet described in any one of 1 to 3 above.
[0031] The annealing separating agent contains a composite oxide in the range of 1 to 10 parts by mass relative to MgO: 100 parts by mass, and the composite oxide contains one or more elements selected from Group 1: Fe, Mn, Al and Ca and Group 2: Zr, Ta, Mo and Nb.
[0032] According to the present invention, since the inhibitor reinforcing element can be fully purified, it is possible to manufacture oriented electromagnetic steel sheets with good magnetic properties, thereby greatly contributing to the improvement of the quality of oriented electromagnetic steel sheets. Detailed Implementation
[0033] The inventors conducted various experiments to improve the purification of orientation-type electromagnetic steel sheets using inhibitor-reinforcing elements. Their latest discovery is that by using a composite oxide containing a specific element as a component of the annealing separating agent, the purification of the inhibitor-reinforcing element can be significantly improved.
[0034] The following describes the experiments that completed this invention.
[0035] A steel billet containing C: 0.07% by mass (hereinafter, the "% by mass" of steel plate composition is simply expressed as "%)", Si: 3.3%, Mn: 0.07%, Al: 0.02%, N: 0.008%, Se: 0.02%, and Nb: 0.005%, with the remainder being substantially Fe, is heated at 1380°C and homogenized for 30 minutes. It is then hot-rolled to a thickness of 2.2 mm, followed by two cold rolling processes with an intermediate annealing at 1050°C for 1 minute, to produce a cold-rolled plate with a final thickness of 0.23 mm.
[0036] After decarburization annealing, the cold-rolled sheet is coated with an annealing separating agent mainly composed of MgO and dried. At this time, various additives are mixed in the annealing separating agent with varying amounts relative to MgO: 100 parts by mass. Next, as the final annealing, a second recrystallization annealing is performed at 890°C for 40 hours, followed by a further purification annealing at 1210°C for 10 hours.
[0037] Then, the unreacted annealing separator is removed, and a mixture of aluminum dihydrogen phosphate and colloidal silica is coated. Simultaneously, planarization annealing at 850°C for 1 minute is performed during sintering to obtain the steel plate of the product.
[0038] The magnetic properties of these steel plates were determined according to JIS C 2550. After removing the coating from the obtained steel plates, quantitative analysis of Nb, N, and C was performed. As analytical methods, Nb and N were analyzed using spectrophotometry, and carbon was analyzed using combustion infrared absorption spectrometry (the same methods apply to the following experiments and examples).
[0039] The results obtained in this way are shown in Table 1.
[0040] [Table 1]
[0041] Table 1
[0042]
[0043] As shown in the table, the addition of MnTa₂O₆ effectively reduced the levels of Nb, N, and C in the steel plate, resulting in excellent purification. Furthermore, the magnetic properties also showed good values. In contrast, the addition of Ta oxide, Mn oxide, or Mn compounds other than composite oxides resulted in little difference from the case where no additives were added to the annealing separator, with almost no purification effect.
[0044] The reason for improving purification by adding a composite oxide containing Mn, Ta, etc. is not yet clear, but the inventors have considered the following.
[0045] During the final annealing, Nb combines with N and precipitates as a nitride, which enhances the inhibition of grain growth. Through this effect, a secondary recrystallized structure with strong aggregation in the Goss orientation is obtained.
[0046] Here, secondary recrystallization grains are generated at around 800–900°C. Furthermore, starting above 900°C, Nb nitride decomposes and separates into dissolved Nb and nitrogen. Nitrogen is purified by diffusing to the surface of the steel plate and exiting from there into the gas phase. On the other hand, dissolved Nb could be purified by being oxidized to Nb₂O₅ by the hydrated water of MgO in the annealing separating agent; however, in practice, since Si, which has a higher ionization tendency than Nb, is abundant in the steel, SiO₂ is preferred, while the formation of Nb₂O₅ is suppressed. Therefore, to purify Nb, methods other than oxidation are needed to fix it. This is because if Nb is not sufficiently purified, N and C will re-diffuse into the steel during the cooling of the final annealing or during subsequent planarization annealing, forming niobium nitride and niobium carbide.
[0047] Here, the MnTa₂O₆ effective for Nb purification has the same crystal structure as the orthorhombic MnNb₂O₆. Therefore, Ta and Nb can substitute for each other. The free energy of MnTa₂O₆ decreases as it dissolves into Mn(Ta,Nb)₂O₆. Therefore, it is believed that Nb substitutes for Ta in the MnTa₂O₆ contained in the annealing separator, diffuses from the steel plate surface into the annealing separator as a solid solution of Mn(Ta,Nb)₂O₆, thus promoting purification.
[0048] Moreover, the replaced Ta does not penetrate into the steel, but exists as Ta ions in the annealing separator, and is purified by final annealing together with MnTa2O6 and Mn(Ta,Nb)2O6, or is removed with the removal of unreacted annealing separator.
[0049] Next, the reasons for limiting the annealing separator for the oriented electromagnetic steel sheet of the present invention will be explained.
[0050] [Annealing Separator]
[0051] The main component of the annealing separator in this invention is MgO. That is, at least 50% by mass of the annealing separator is MgO.
[0052] The aforementioned annealing separating agent contains a composite oxide comprising oxides of at least one element selected from Group 1: Fe, Mn, Al, Ca, and Group 2: Zr, Ta, Mo, Nb. By using such a composite oxide, even when inhibitory reinforcing elements such as Nb, Ti, Ta, and V are added to the steel, they can be purified during the final annealing process.
[0053] It should be noted that, as described above, the key to such composite oxides is that they possess a crystal structure capable of interchanging with inhibitory reinforcing elements such as Nb, Ti, Ta, and V. From the viewpoint of ease of operation and acquisition, oxides of at least one element from each of the aforementioned groups 1 and 2 are preferred as compounds possessing such crystal structures.
[0054] Specifically, for example (Fe) x Mn 1-x MoO4, (Fe x Mn 1-x )2Mo3O 12 Al2(MoO4)3, (Fe x Mn 1-x (Ta) y Nb 1-y O3, (Fe x Mn 1-x )2ZrO5, Al2Zr3O9. Here, since Fe and Mn, and Nb and Ta can be completely dissolved in each other, x and y can take any values in the range of 0 to 1. Furthermore, the preferred composite oxide is (Fe) which is easily reinforced by solid solution inhibitors. x Mn 1-x (Ta) y Nb 1-y )2O6, CaZrO3, Al2Mo3O 12 、CaMoO4.
[0055] The content of the aforementioned composite oxide in the annealing separator is 1 to 10 parts by mass relative to MgO: 100 parts by mass, preferably 2 parts by mass or more, more preferably 3 parts by mass or more, and even more preferably 9 parts by mass or less, more preferably 8 parts by mass or less. When the content is less than 1 part by mass relative to MgO: 100 parts by mass, purification effect is not obtained; if it exceeds 10 parts by mass, the MgO ratio decreases, resulting in poor film formation.
[0056] In the annealing separator of the present invention, from other viewpoints such as magnetic properties and film coating properties, the additives described below can be further used.
[0057] Specifically, conventionally known additives include borates, carbonates, sulfates, oxides, hydroxides, nitrates, halides, and phosphates of Li, Na, K, Mg, Sr, Ca, Ba, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Si, Cu, Sb, Pb, Sn, Al, Bi, Nb, Mo, W, and lanthanides. Only one of these additives may be used, or two or more may be used in combination. It should be noted that the amount of the above additives added relative to MgO: 100 parts by weight is preferably 0.01 to 15 parts by weight. This is because if too little is added, the effect will be insufficient; on the other hand, if too much is added, it will excessively promote film formation, or only the surface inhibitor will be excessively enhanced, which may easily lead to a deterioration of magnetic properties and the film.
[0058] In the manufacturing method of this invention, the annealing release agent is applied to the surface of a steel plate using conventional methods. The most common method involves slurrying the annealing release agent with an appropriate amount of water, applying it using a roller coater, and then drying it. Alternatively, methods such as electrostatic coating, spraying, or die coating using a coating machine can also be used.
[0059] The application amount of the annealing release agent can be determined using conventional methods, for example, by weight (excluding water) of 0.5–30 g / m² per two sides. 2 Left or right is fine.
[0060] It should be noted that the amount of annealing release agent applied in this specification is expressed as the weight of each two sides in an anhydrous state.
[0061] Next, the reasons for the limitations and preferred conditions for the composition and manufacturing conditions of the steel billet are explained.
[0062] [Composition of steel billet]
[0063] C: 0.01~0.09%
[0064] C is an element that promotes texture improvement, and a good texture cannot be formed if its content is outside the above range. Therefore, its content is 0.01% to 0.09%, preferably 0.02% or more, more preferably 0.03% or more, even more preferably 0.08% or less, and more preferably 0.07% or less.
[0065] Si: 2.00~4.00%
[0066] Si is an element that improves magnetic properties. When its content is less than 2.00%, the effect of reducing iron loss is weakened, and if it exceeds 4.00%, it impairs cold rollability. Therefore, its content is 2.00% to 4.00%, preferably 2.30% or more, more preferably 2.50% or more, even more preferably 3.80% or less, and more preferably 3.50% or less.
[0067] Mn: 0.03~0.25%
[0068] Mn is an element required to improve the hot workability of steel. When the content is less than 0.03%, the aforementioned effect is insufficient; on the other hand, if it exceeds 0.25%, the magnetic flux density of the product plate decreases. Therefore, the Mn content is in the range of 0.03% to 0.25%, preferably 0.06% or more, more preferably 0.08% or more, even more preferably 0.22% or less, and more preferably 0.20% or less.
[0069] Nb, V, Ti: The total of any one or more of them is 0.002% to 0.025%.
[0070] Nb, V, and Ti are elements used to enhance the inhibitor. If their combined content is less than 0.002%, there is no effect; if it exceeds 0.025%, it is difficult to achieve sufficient purification of these elements even with the application of this invention. Their combined content is preferably 0.005% or more, more preferably 0.010% or more, even more preferably 0.020% or less, and more preferably 0.018% or less.
[0071] In addition to these components, AlN, MnS, and MnSe are well-known as common inhibitors of oxidative stress. Any one of these can be used in this invention, or two or more can be used in combination.
[0072] Furthermore, in this invention, as an auxiliary inhibitor, any one or more of Ni, Cr, Cu, P, Sb, Sn, Bi, Mo, B, and Te can be used. These elements are those that do not form precipitates and therefore do not require purification or are easily purified.
[0073] The contents of the above elements are as follows: Al: 0.004–0.040%, N: 0.002–0.010%, S: 0.002–0.030%, Se: 0.002–0.030%, Ni: 0.01–1.50%, Cr: 0.01–0.50%, Cu: 0.01–0.50%, P: 0.005–0.100%, Sb: 0.005–0.100%, Sn: 0.005–0.100%, Bi: 0.001–0.050%, Mo: 0.005–0.100%, B: 0.0002–0.0025%, Te: 0.0005–0.0100%. It should be noted that the Mn content is as described above.
[0074] If their content is lower than the above-mentioned range, there is no effect; on the other hand, if it is higher than the above-mentioned range, the inhibitory force is too strong and secondary recrystallization becomes unstable. Therefore, the above-mentioned range is set.
[0075] The remaining components of the steel billet are Fe and unavoidable impurities, which are also described in this specification as "substantially composed of Fe".
[0076] [Manufacturing Conditions]
[0077] A steel billet having the above-mentioned preferred composition is heated and hot-rolled according to a known method, and then cold-rolled once or multiple times with intermediate annealing to produce a final cold-rolled sheet of the final thickness. It should be noted that, if necessary, the hot-rolled sheet may also be annealed after hot rolling.
[0078] The cold-rolled sheet undergoes a recrystallization annealing, followed by coating with the annealing separating agent of the present invention and then undergoing a final annealing. The final annealing can be performed using a known method consisting of a secondary recrystallization annealing and a subsequent purification annealing at a higher temperature. For example, the secondary recrystallization annealing can be performed at a temperature of 800°C to 1100°C for 5 to 200 hours. If the above-mentioned time is maintained within the above temperature range, the secondary recrystallization annealing can be performed while simultaneously increasing the temperature for subsequent purification annealing. Purification annealing is typically performed at a maximum reaching temperature of around 1200°C, but setting the maximum reaching temperature to 1210°C, preferably 1230°C or higher, can further promote purification. The purification annealing time at or above 1200°C is preferably 1 hour or more, more preferably 3 hours or more. There is no particular limitation on the upper limit of the maximum reaching temperature, but from the viewpoint of preventing poor roll shape, it is preferably less than 1250°C. Similarly, the upper limit of the purification annealing time is preferably 30 hours or less, more preferably 20 hours or less, for the time required to reach or above 1200°C.
[0079] Then, an insulating coating containing colloidal silica can be further applied, followed by an insulating tension coating treatment that simultaneously performs planarization annealing and sintering. This process yields an orientation-oriented electromagnetic steel sheet with excellent magnetic and coating properties. It should be noted that, if necessary, magnetic domain refinement can also be performed using lasers, electron beams, or other methods.
[0080] Furthermore, in the manufacturing method of the present invention, conventional methods can be used for any manufacturing conditions not described in this specification.
[0081] Example
[0082] [Example 1]
[0083] A steel billet containing 0.06% C, 3.40% Si, 0.08% Mn, 0.006% Al, 0.020% Sb, 0.010% Ti, 0.003% N, and 0.03% Cr, with the remainder essentially composed of Fe, is heated at 1250°C for 40 minutes and then hot-rolled to a thickness of 2.0 mm. It is then hot-rolled and annealed at 1000°C for 60 seconds. Next, it is cold-rolled using a continuous rolling mill to produce a steel sheet with a final thickness of 0.23 mm. After decarburization annealing, the steel sheet is coated with an annealing release agent, dried, and then wound into coils.
[0084] The annealing separating agent used is composed of 2 parts by mass of titanium dioxide and 1 part by mass of magnesium sulfate for every 100 parts by mass of the main agent (MgO), or, further, the composite oxide MnTa2O6 or various oxides are added at concentrations of 13 g / m³. 2 It is coated on both sides of the steel plate.
[0085] Then, as a final annealing, a secondary recrystallization annealing was performed by increasing the temperature from 800°C to 1100°C at a rate of 10°C / h, followed by a purification annealing at 1200°C or higher for 10 hours, with a maximum temperature reaching 1230°C. Next, an insulating coating was applied, and after thermal planarization, the mixture was sintered at 900°C for 60 seconds, followed by magnetic domain refinement treatment using electron beam irradiation.
[0086] The magnetic properties of the above-mentioned products are shown in Table 2. In addition, after removing the coating from the steel plate, quantitative analysis of Ti, N, and C was performed, and the results are also recorded in this table.
[0087] [Table 2]
[0088] Table 2
[0089]
[0090] As can be seen from the table, as described above, the purification of Ti and N is effectively carried out in an annealing separator containing an appropriate amount of composite oxide suitable for the present invention, and as a result, the magnetic properties are also improved.
[0091] [Example 2]
[0092] A slab containing 0.07% C, 3.28% Si, 0.07% Mn, 0.02% Al, 0.008% N, 0.02% S, and 0.01% V, with the remainder essentially composed of Fe, was heated to 1400°C and then hot-rolled to a thickness of 2.2 mm. It was then cold-rolled twice, with intermediate annealing at 1100°C for 1 minute, to a final thickness of 0.23 mm. After decarburization annealing of this cold-rolled sheet, an annealing separating agent containing 5 parts by mass of CaMoO4 and 0.2 parts by mass of potassium borate relative to 100 parts by mass of MgO was added at 11 g / m³. 2 The coating was applied to both sides of the steel sheet. It should be noted that, as a comparative example, the same steel sheet was also manufactured simultaneously, except that CaMoO4 was not used. Then, as a final annealing, a secondary recrystallization annealing was performed at 820°C for 50 hours, followed by a purification annealing at various maximum temperatures for 5 hours in a dry H2 atmosphere. Next, an insulating coating was applied, and heat planarization was performed while sintering at 900°C for 60 seconds. The magnetic properties of the above product are shown in Table 3. Furthermore, after removing the coating from the steel sheet, quantitative analysis of V, N, and C was performed, and the results are also recorded in this table.
[0093] [Table 3]
[0094] Table 3
[0095]
[0096] As can be seen from the table, the purification of V was further promoted by increasing the maximum purification temperature to above 1210℃.
[0097] [Example 3]
[0098] The slabs composed of the components shown in Table 4 were heated to 1400°C and hot-rolled to a thickness of 2.2 mm. They were then subjected to two cold rolling processes, with intermediate annealing at 1050°C for 2 minutes between each cold rolling process, to achieve a final thickness of 0.23 mm. After decarburization annealing of the cold-rolled sheet, an annealing separating agent containing 3 parts by mass of (Fe,Mn)Nb₂O₆, 3 parts by mass of tin oxide, and 2 parts by mass of titanium oxide (relative to 100 parts by mass of MgO) was added at a concentration of 10 g / m². 2 The coating was applied to both sides of the steel sheet and dried. It should be noted that, as a comparative example, the same steel sheet was also manufactured simultaneously, except that (Fe,Mn)Nb₂O₆ was not used. Then, as a final annealing, a secondary recrystallization annealing was performed at 820°C for 50 hours, followed by purification annealing at 1230°C for 5 hours in a dry H₂ atmosphere. Next, an insulating coating was applied, and the mixture was heat-planarized while sintering at 900°C for 60 seconds. The magnetic properties of the above products are recorded in Table 4. Furthermore, after removing the coating from the steel sheet, quantitative analysis of Nb, V, Ti, N, and C was performed, and the results are also recorded in this table.
[0099]
[0100] As can be seen from the table, any steel plate with the composition within the scope specified in this application was fully purified and obtained good magnetic properties under the condition of using an annealing separating agent containing a specified amount of (Fe,Mn)Nb2O6.
Claims
1. A method for manufacturing an orientation-oriented electromagnetic steel sheet, characterized in that, The oriented electromagnetic steel sheet is heated in a slab, hot-rolled, cold-rolled once or twice or more with intermediate annealing, recrystallization annealed once, and then coated with an annealing separating agent and finally annealed. The slab blank for the orientation-oriented electromagnetic steel sheet has the following components. Composition: Contains C: 0.01–0.09% by mass, Si: 2.00–4.00% by mass, Mn: 0.03–0.25% by mass, further containing a total of 0.002–0.025% by mass of one or more elements selected from Nb, V, and Ti, with the remainder being Fe and unavoidable impurities. The annealing separating agent is mainly composed of MgO, and contains 1 to 10 parts by mass of a composite oxide relative to MgO: 100 parts by mass. This composite oxide is selected from (Fe... x ,Mn 1-x )2Mo3O 12 、(Fe x ,Mn 1-x (Ta) y ,Nb 1-y )O3, Al2Zr3O9, FeTa2O6, MnNb2O6, (Fe,Mn)Nb2O6, MnTa2O6, CaZrO3 and Al2Mo3O 12 , where x and y take any value in the range of 0 to 1.
2. The method for manufacturing the oriented electromagnetic steel sheet according to claim 1, wherein, The maximum temperature reached for the final annealing is set to 1210°C or higher.
3. The method for manufacturing the oriented electromagnetic steel sheet according to claim 1 or 2, wherein, In addition to the aforementioned composition, the slab for the oriented electromagnetic steel sheet further contains one or more of the following: Al: 0.004–0.040 wt%, N: 0.002–0.010 wt%, S: 0.002–0.030 wt%, Se: 0.002–0.030 wt%, Ni: 0.01–1.50 wt%, Cr: 0.01–0.50 wt%, Cu: 0.01–0.50 wt%, P: 0.005–0.100 wt%, Sb: 0.005–0.100 wt%, Sn: 0.005–0.100 wt%, Bi: 0.001–0.050 wt%, Mo: 0.005–0.100 wt%, B: 0.0002–0.0025 wt%, and Te: 0.0005–0.0100 wt%.
4. An annealing separating agent, characterized in that, It is the annealing separating agent used in the manufacturing method of the oriented electromagnetic steel sheet according to any one of claims 1 to 3. The annealing separating agent contains 1 to 10 parts by mass of a composite oxide relative to MgO: 100 parts by mass, and the composite oxide is selected from (Fe x ,Mn 1-x )2Mo3O 12 、(Fe x ,Mn 1-x (Ta) y ,Nb 1-y )O3, Al2Zr3O9, FeTa2O6, MnNb2O6, (Fe,Mn)Nb2O6, MnTa2O6, CaZrO3 and Al2Mo3O 12 , where x and y take any value in the range of 0 to 1.
Citation Information
Patent Citations
Forsterite film of grain oriented silicon steel sheet with high magnetic flux density and its formation
JP1997184017A
Method for purification annealing of grain oriented silicon steel sheet
JP1999158557A
Method for producing grain-oriented magnetic steel sheet having good film-external appearance
JP2006193798A
Method for producing grain-oriented electrical steel sheet excellent in productivity
JP2008115421A
Method for manufacturing grain-oriented magnetic steel sheet superior in magnetic property and stamping property
JP2003253334A